Relationship between spiritual quotient and self-adjustment of students at Jabal Nor Islamic Boarding School, Sidoarjo, Indonesia - Khamida Khamida; Rizqy Mubarak; Syiddatul Budury (AOSIS, 2019)
Adjusting to a life at Islamic boarding schools can be a very unique experience, many students are struggling and trying to cope with this new situation. The purpose of this research was to determine the correlation between spiritual quotient and the adjustment of student at Islamic Boarding School. The analysis method involved a cross sectional approach, with a population size was 60 students of class VII, who live in boarding school. Furthermore, a large sample size of 53 people was selected; using simple random technique, with the independent variable being spiritual quotient and the dependent was self-adjustment. Data analysis used a Chi-Square test, where hipotesis H1 is accepted if ρ < α = 0.05. The results showed that all respondents, who had low spiritual quotient, possessed a negative self-adjustment compared with other respondents. Chi-Square statistical test results, with a significant level α = 0.05 obtained the value of p (0.000), indicating a relationship between spiritual quotient and adjustment. In conclusion, a better spiritual quotient possessed by student, affects the process of adjustment